Aluminothermic welding modeling of heavy haul rails using the element birth and death technique. Issue 10 (3rd October 2022) - Lima, E. A.; Bertelli, F.; Dias, A. P. C.; Santos, A. A.
Abstract: The aluminothermic welding process (ATW) of rail tracks is the most used in the field due to its low cost, execution time, and light equipment. In recent years, some experimental and numerical models have been developed to study ATW. The accuracy of the models is still being demonstrated. In this work, a new three-dimensional thermoelastoplastic numerical model of the ATW process is proposed. This model uses the Element Birth and Death (EBD) technique with Ansys® software to accurately simulate filling the pouring region with filler metal. The thermal and mechanical phenomena of all stages of a conventional rail track welding process were considered, as well as the effects of the material's phase transformations during the process. First, the validation was carried out with experimental and numerical data from studies available in the literature for UIC60 rails. Then, the validated model was applied in the simulation of welding a TR68-type rail and an unprecedented analysis of the residual stresses resulting from this type of rail was performed. The ATW process could then be simulated using significantly fewer elements than the numerical models available in the literature and proved to be applicable for the study of the ATW process of railway tracks.